KALAPAN SEBAGAI UNSUR EKONOMI KREATIF PADA JARANAN BROMO-TENGGER-SEMERU (BTS): TUMPANG - E. Wara Suprihatin DP; Ika Wahyu Widyawati; Robby Hidajat (Jurnal Istiqro, 2022)
Jaranan Bromo-Tengger-Semeru (BTS): Tumpang places the kalapan/trance session as the highlight of an attractive event and becomes an element of the creative economy that significantly contributes to the actors and their community. This research aims to describe how dancers can experience insanity and why the kalapan session is an element of the creative economy. The research method used is a qualitative approach with a multi-case study in two different settings. Collecting data through interviews, observation and documentation on two groups of jaranan, namely 1) Anusopati and 2) Tugu Sari Panggung Rejo. Data is verified by source triangulation data triangulation to obtain validity for efforts to prepare the episode of kalapan, the main attraction in Jaranan BTS: Tumpang. The results of the study: 1) some rituals must be carried out and followed to become a Jaranan dancer who can go crazy/trance, namely the nyetren ritual which is routinely carried out every Friday Legi, 2) the episode of kalapan/trance is a part that has extraordinary appeal, is magical, mystical and attractiveness that always manages to bring in many spectators and many traders in the venue. The trance dancer is not in a state of pretending, but is indeed possessed by a supernatural spirit invited and entered by the handler. This research is expected to be a helpful reference on the existence of a process for infatuation/introduction that can be an element of the creative economy for the community of actors, fans and the general public. This research also expected as supporting data for writing the E-Book Jaranan Bromo-Tengger-Semeru (BTS): Tumpang.